Importance of Nest Attributes in the Conservation of Endemic Birds of the Juan Fernández Archipelago, Chile - Vergara-Egert, P (2011)
Understanding the particular nesting ecology of island endemic species represents the first step in identifying suitable micro-habitats and establishing efficient management programmes. This could become even more important when island bird assemblages are prone to invasion by ecologically similar species that may eventually cause niche compression or the extirpation of species already present on the island. In this study we describe the nesting ecology of both native and introduced landbird species of the Juan Fernández Islands and determine the extent to which native species could be negatively affected by alien competitors. A total of 119 nests belonging to the 11 resident landbird species were analysed. Landbirds exhibited a wide range of nesting habitat preferences on the different islands, covering different vegetation types, altitudes and ecosystems. By means of a cluster analysis we determined that competition between alien and endemic species apparently does not represent an important factor affecting resource use by endemic birds. Endemic landbirds preferred sites comparatively higher above the ground, with a greater slope and a larger level of shelter, than alien species. The introduced hummingbird, the Green-backed Firecrown Sephanoides sephaniodes, had different nesting preferences to the endemic Juan Fernandez Firecrown S. fernandensis, whereas the House Sparrow Passer domesticus selected nest sites located in populated areas, suggesting that both alien species may not be competing with endemic passerines for nest sites. However, urgent measures are necessary to reduce the potential predation risk on Juan Fernandez Firecrown nests by the alien Austral Thrush Turdus falcklandii. © 2011 BirdLife International.